1981
DOI: 10.1080/10862968109547400
|View full text |Cite
|
Sign up to set email alerts
|

Where Do Their Answers Come from? A Study of the Inferences which Children Make when Answering Questions about Narrative Stories

Abstract: Abstract. Young readers often seem to overlook explicitly stated causal statements in narrative texts and instead give their own versions of why a text event occurred. Some researchers would agree with Smith (1979) that children do this because they read for meaning rather than word-by-word. This is an "inside-out" (or, "schema-based") view of text comprehension. Other researchers, however, agree with Thorndike (1917) that "errors" occur because "the mind is assailed by every word in the paragraph." This is an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

1987
1987
2005
2005

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
1
6
0
2
Order By: Relevance
“…The study conducted by Nicholson and Imlach (1981) with 8-year-old children also indicated that young readers sometimes trust more in their prior knowledge than in what the text states. The children (average or above-average readers) read stories that included explicit causal statements about the reason for the events described in the texts.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…The study conducted by Nicholson and Imlach (1981) with 8-year-old children also indicated that young readers sometimes trust more in their prior knowledge than in what the text states. The children (average or above-average readers) read stories that included explicit causal statements about the reason for the events described in the texts.…”
Section: Introductionmentioning
confidence: 88%
“…In contrast to Nicholson and Imlach (1981) and McCormick (1992) the comprehension questions in the present study were presented orally, since having to write their answers may limit the extent to which young children can express themselves. Indeed, McCormick reports that she was unable to use a substantial proportion of the children's (written) responses, because they were insufficiently precise.…”
Section: Aims Of the Studymentioning
confidence: 96%
See 1 more Smart Citation
“…Sličan zaključak izveli su i drugi istraživači -deca koja imaju teškoću da razumeju pročitani sadržaj imaju problem da integrišu informacije iz teksta sa prethodnim znanjima (McCormic, 1992). Prema Mekormiku, dva su moguća uzroka tog problema: (1) neka deca se previše oslanjaju na ranija znanja, zanemarujući tako relevantne informacije prezentovane u tekstu koji čitaju (videti takođe: Nicholson & Imlach, 1982); (2) neka deca se prekomerno oslanjaju na ono što je u tekstu eksplicitno dato, ne pokušavajući da izvedu zaključke na osnovu znanja koja imaju. Diskusiji o korišćenju ranijih znanja prilikom čitanja teksta i izgrađivanja njegovog razumevanja treba dodati i interpretaciju prema kojoj deca odgovaraju na pitanja o tekstu oslanjajući se prvenstveno na prethodna znanja, zanemarujući poruke koje tekst prenosi, onda kada nisu sigurna u pogledu odgovora koji treba da daju, a ne žele da kažu da nešto ne znaju, odnosno ne razumeju (Brandão & Oakhill, 2005).…”
Section: Komponente čItalačke Pismenosti I Faktori Koji Deluju Na Njiunclassified
“…Nema, dakle, podataka na osnovu kojih bismo mogli izvesti zaključak da se deca pozivaju na svoja lična iskustva i prethodna znanja, zanemarujući pročitani tekst, što je bio zaključak jednog dela istraživača iz ove oblasti. Da podsetimo, nalazi nekih studija ukazali su na to da do teškoća prilikom čitanja, između ostalog, dolazi zato što se deca previše oslanjaju na ranija znanja, zanemarujući relevantne informacije iznete u tekstu koji čitaju (Nicholson & Imlach, 1982;McCormic, 1992). Sa druge strane, u uvodnom delu teksta ukazali smo i na nešto drugačije nalaze koji su pokazali da su takve teškoće prilično retke (postoje u svega 6,46% dečijih odgovora) (Brandão & Oakhill, 2005).…”
Section: Da LI Se Kroz Simetričnu Vršnjačku Interakciju Može Unapređiunclassified